2002
DOI: 10.1046/j.1471-4159.2002.01157.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal oxidative damage from activated innate immunity is EP2 receptor‐dependent

Abstract: Increase in prostaglandin (PG) E 2 levels and oxidative damage are associated with diseases of brain that involve activation of innate immunity. We tested the hypothesis that cerebral oxidative damage resulting from activation of innate immunity with intracerebroventricular (icv) lipopolysaccharide (LPS) is dependent on PGE 2 -mediated signaling. We measured two quantitative in vivo biomarkers of lipid peroxidation: F 2 -isoprostanes (IsoPs) that derive from arachidonic acid (AA) that is uniformly distributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
143
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 127 publications
(151 citation statements)
references
References 55 publications
8
143
0
Order By: Relevance
“…The earliest time point evaluated in KA-induced excitotoxicity was 30 min since seizures start immediately after the icv KA injection. Elevated levels of these in vivo markers of oxidative damage are in agreement with our previous findings (Montine et al, 2002;Milatovic et al, 2005;Gupta et al, 2007), as well as by others (Patel et al, 2001) and indicate that KA injection leads to profound cerebral and neuronal oxidative damage in mice.…”
Section: Discusionsupporting
confidence: 92%
See 1 more Smart Citation
“…The earliest time point evaluated in KA-induced excitotoxicity was 30 min since seizures start immediately after the icv KA injection. Elevated levels of these in vivo markers of oxidative damage are in agreement with our previous findings (Montine et al, 2002;Milatovic et al, 2005;Gupta et al, 2007), as well as by others (Patel et al, 2001) and indicate that KA injection leads to profound cerebral and neuronal oxidative damage in mice.…”
Section: Discusionsupporting
confidence: 92%
“…It was also reported that NO inhibits neuronal energy production in cultured hippocampal neurons (Brorson et al, 1999), leading to rapid ATP depletion. In addition, increased production of NO in the presence of the superoxide anion radical (O 2 − ) may generate peroxynitrite radical (OONO − ) (Montine et al, 2002;Milatovic et al, 2002), a potent inducer of lipid peroxidation.…”
Section: Discusionmentioning
confidence: 99%
“…The increased toxicity of LPS with addition of EP2/EP3 receptor agonists is relevant to recent in vivo studies demonstrating that in the setting of inflammation, prostaglandin receptor signaling can exhibit an opposite and toxic effect on neurons. For example, in the LPS model of innate immunity, the EP2 receptor mediates a major component of inflammatory oxidative stress and secondary synaptotoxicity [17,19]. One potential mechanism is via induction of iNOS, production of NO, and production of reactive oxygen species; alternatively, microglialderived NO may lead to presynaptic release of glutamate and excitotoxic injury.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that the EP2 receptor enhances inflammatory oxidative stress and synaptotoxicity in innate immunity [17,19] and in a transgenic model of Familial AD [13]. These effects are distinct from the neuroprotective function of the EP2 receptor seen both in vitro in organotypic slices and in vivo in models of cerebral ischemia [15,16].…”
Section: Opposing Effect On Neuronal Viability By Ep Receptor Activatmentioning
confidence: 99%
See 1 more Smart Citation